Palm Oil Current Status and Updates - Waisundara, Viduranga Y. (IntechOpen, 2023)
The palm oil industry is one of the oldest and most established commercial industries in the world. The product is hailed as an economically viable crop as compared with other oils used and consumed globally. This book provides an overview of the palm oil industry and the management of the crop itself. There has always been a growing interest in the scientific community to better understand this crop as well as the related industrial processes for environmental and nutritive purposes. As such, this book presents useful information on the palm oil industry from multiple perspectives.